Produção de mudas cítricas e perspectivas para citricultura brasileira - Oliveira, Mateus Borges de (Universidade Federal de São Carlos, 2026)
The citrus industry is one of the main activities of Brazilian agribusiness, playing an essential role in generating income, employment, and foreign exchange for the country. This study aimed to analyze the technical and legal aspects involved in the production of citrus nursery plants, as well as to discuss the perspectives and challenges of the Brazilian citrus sector, in order to inform production practices that ensure phytosanitary quality and sector sustainability. Through an integrative literature review, information was gathered from scientific publications, legislation, and technical reports issued by institutions such as MAPA, Embrapa, and Fundecitrus. It was observed that the mandatory use of screened nurseries for citrus seedling production initially established in the state of São Paulo and later extended Nationwide represented a milestone in the modernization of the sector, reducing the spread of diseases such as Citrus Variegated Chlorosis (CVC) and huanglongbing (HLB). The importance of using certified mother plants, implementing sanitary indexing, and applying improved grafting techniques and protected-environment management was also verified. The adoption of rootstocks such as citrandarins and Swingle citrumelo has contributed to greater disease resistance and better adaptation to different edaphoclimatic conditions. Furthermore, the expansion of citrus cultivation into new regions such as Goiás, Mato Grosso do Sul, Bahia, and Paraná reflects not only the search for areas with lower HLB incidence but also economic and structural factors that influence the productive reorganization of the sector. It is concluded that the integration of technology, legislation, and sustainable management is fundamental to ensuring seedling health, competitiveness, and the long-term sustainability of the Brazilian citrus industry.
Production of citrus seedlings and perspectives for Brazilian citrus farming
Keywords: Legislação; Fitossanidade; Rootstocks; Screened nurseries; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; 2. Fome Zero e Agricultura Sustentável